FCE Practice Exam Papers 2. For the Cambridge English First FCE/FCE(fs) Examination: [student's book] - Evans V. Virginia (Newbury, Express Publishing, 2021)
The book is aimed at learners of the English language at CEF level B2 preparing for the Cambridge English First FCE/FCE(fs) Examination or any other examinations at the same level of difficulty. The book consists of: 10 complete practice tests written in the same format as the examination itself. Further practice on Word Distractors, Open Cloze Sentences, Key Word Transformations and Word Formation. Glossary of all words tested in Paper 1 - Part 1 as well as in the Further Practice section.